Mutant vary region of pncA gene sequence of pyrazinamide resistance among multidrug resistant Mycobacterium tuberculosis isolates - Titiek sulistyowati; Soedarsono; Ni Made Mertaniasih (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2022)
ABSTRACT Introduction: Pyrazinamide (PZA) is one of the potent front-line drugs that act as antituberculosis (antiTB) for nonresistant or resistant Mycobacterium tuberculosis. Mutation of pncA gene is considered to be main target of PZA resistance mechanism. This study aims to determine the mutant gene sequences, location, and correlation of pncA gene mutations with PZA resistance in MDR Mycobacterium tuberculosis as a base for the rapid molecular examination. Objective: This study aims to determine the mutant gene sequence and location of pncA gene with PZA resistance in multidrug resistant (MDR) Mycobacterium tuberculosis need a rapid molecular examination for consideration of MDR TB therapy management in Indonesia. Methods: MDR Mycobacterium tuberculosis were identified and tested for PZA resistance with BACTEC MGIT 960 as a gold standard, followed by DNA extraction, PCR amplification and pncA gene sequencing. Results: An analysis of 561 bp sequence of nucleotides was performed to determine type and location of mutations. A total of 35 isolates of this study showed 14 isolates of pncA gene mutation (40%), and revealed in 13 resistant and 1 sensitive isolate. The correlation analysis of pncA gene mutation to PZA resistance was significant (p = 0,003 and r = 0,452). Mutations in 3 (three) specific regions of pncA gene are 1 isolate at codons 51-76, 1 isolate at codons 130-142, and 3 isolates at codons 163-180. Conclusion: Types of mutations in the pncA gene include substitution of 11 isolates, insertion of 2 isolates, and no deletion. Insertion of 178 CGCGCTGGAGGAGATGCGCACCGCC and multiple mutations in one isolate.